Rethinking the good life amid the ecological crisis: The interplay between eco‐anxiety, nature connection and well‐being - Miia Grénman; Jussi Nyrhinen; Panu Pihkala; Antti Honkanen; Juulia Räikkönen (People and Nature)
Abstract The ecological crisis, characterized by various interconnected environmental problems, has emerged as a significant source of anxiety, commonly known as ‘eco‐anxiety’. This psychological distress stemming from ecological threats carries profound implications for human and nonhuman well‐being. Research suggests that while a strong connection with nature can increase eco‐anxiety, cultivating and sustaining this connection can also serve as a coping mechanism to mitigate its negative effects. This study investigates the interplay between eco‐anxiety, nature connection and well‐being, providing a framework for understanding how they interact amid the ecological crisis. The data were collected through an online panel survey in 2022, targeting the Finnish population aged 18 to 65 (n = 1013). Covariance‐based structural equation modelling (CB‐SEM) was employed to test three hypotheses regarding the relationship between these constructs. The analysis confirmed all hypotheses. First, eco‐anxiety was negatively related to well‐being, indicating that ecological threats contribute to psychological distress. Second, a positive association was found between eco‐anxiety and nature connection, suggesting that individuals experiencing eco‐anxiety possess a deeper sense of interconnectedness with the natural world. Third, a positive relationship was established between nature connection and well‐being, highlighting that a robust connection with nature enhances overall well‐being. Additionally, a statistically significant positive indirect relationship was identified between eco‐anxiety and well‐being, indicating that a deeper connection with nature can mitigate the negative effects of eco‐anxiety. Synthesis and applications. This study furthers the understanding of the complex interconnections between eco‐anxiety, nature connection and well‐being. The study also advances the understanding of eco‐anxiety not only as a psychological burden but also as a potential catalyst for fostering environmental awareness and engaging individuals in environmental stewardship and agency, sometimes called ‘practical eco‐anxiety’. This holds significant implications for environmental education, psychology and policy development: with constructive coping skills, people can practice environmental responsibility and cherish a strong nature connection. Read the free Plain Language Summary for this article on the Journal blog.